Multidimensional Scaling Method and Some Practical Applications - , B. Manjunatha, Appaji Pundalik Naik, K. R. Mahendra, Manju Prem S., Gunashekhar H., N. R. Kiran, Damodhara G. N., Karthik R. (Archives of Current Research International, 2024)
Multi-Dimensional Scaling (MDS) is a data visualization method that identifies clusters of points by representing the distances or dissimilarities between sets of objects in a lower-dimensional space. This paper explores the theoretical concepts of MDS, various methods of implementation, and the analytical processes involved. Emphasis is placed on the "Stress" function, a goodness-of-fit metric that quantifies the discrepancy between distances in high-dimensional and lower-dimensional spaces. Practical examples and detailed procedures for implementing MDS using MS-Excel and R are provided to enhance understanding. The paper also discusses the use of Scree-plots for determining the optimal number of dimensions. Applications of MDS in different fields, including marketing, ecology, molecular biology, and social networks, are presented with examples on Perceptions of Nations data and Morse code confusion data. Additionally, as a significant contribution, a case study on factors affecting agricultural productivity is included. The versatility and utility of MDS in simplifying complex data and facilitating better decision-making are demonstrated through these practical applications and software implementations.